2007
DOI: 10.1093/ndt/gfm510
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of beta-trace protein and its association to diuresis in haemodialysis patients

Abstract: BTP serum levels may serve as a surrogate marker for residual renal function since HD and HDF do not exert clinical relevant alterations on them. Furthermore, BTP serum concentrations appear strongly associated to RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 17 publications
2
44
0
1
Order By: Relevance
“…Similar to cystatin C and other low molecular weight proteins, BTP is freely filtered by the glomerulus, and it is completely reabsorbed and metabolized by the proximal tubule (37). Serum BTP levels increase as urine output declines in hemodialysis patients (16). BTP is not removed by low-or high-flux hemodialysis membranes during conventional hemodialysis (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to cystatin C and other low molecular weight proteins, BTP is freely filtered by the glomerulus, and it is completely reabsorbed and metabolized by the proximal tubule (37). Serum BTP levels increase as urine output declines in hemodialysis patients (16). BTP is not removed by low-or high-flux hemodialysis membranes during conventional hemodialysis (16).…”
Section: Discussionmentioning
confidence: 99%
“…Serum BTP levels increase as urine output declines in hemodialysis patients (16). BTP is not removed by low-or high-flux hemodialysis membranes during conventional hemodialysis (16). Hemodiafiltration, a specialized type of dialysis not performed for maintenance dialysis in the United States, can remove BTP (16,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 b trace protein (BTP) has recently emerged as another alternative filtration marker. [11][12][13][14][15] BTP is a low molecular weight glycoprotein that is freely filtered by the glomerulus, and has minimal nonkidney elimination. 14 Some studies have suggested that BTP is more accurate than creatinine in estimating measured GFR 11,[13][14][15][16][17][18][19][20][21] and is more strongly associated with CVD.…”
mentioning
confidence: 99%